Geochemical estimation of soils and vegetation of Maladziečna - Karpichenka, Aliaksandr A.; Chartko, Mikalai K.; Semianiuk, Aliaksandr S. (Journal of the Belarusian State University. Geography and Geology, 2019)
The article considers the influence of technogenic conditions on the soil and vegetation cover of Maladziečna city. The study was carried out by sampling soil and vegetation. The total content of chemical elements (Cu, Pb, Mn, Ni, Sn, Ti, Cr) was determined by atomic emission spectrometry. The average content of Cu in the upper soil horizons of Maladziečna is 17.5 mg/kg; Pb – 18.7; Mn – 460.0; Ni – 11.0; Sn – 3.6; Ti – 1986; Cr – 36.5 mg/kg. The content of almost all investigated elements is highly variable (coefficients of variation from 36.4 to 59.7 %), with the exception of Ni with a very high variability (87.6 %). The maximum permissible concentrations were registered for Cu, Pb, Ni and Cr, mostly contaminated is production and storage area and adjacent areas near the railway station in the west of the city, as well as near the metalware factory in the northern part of Maladziečna. In the vegetation of Maladziečna the content of the investigated elements was characterized by high variability for Sn and Cu (V = 39.8 % and V = 54.3 %, respectively), very high for Ni (75.0 %), Cr (85.3 %) and Pb (87.5 %), anomalous for Ti (101.6 %) and Mn (182.1 %). The average geometric content of elements in plant ash: Cu is 19.6 mg/kg; Pb – 2.63; Mn – 303.0; Ni – 3.70; Sn – 0.71; Ti – 232.0; Cr – 9.5 mg/kg. The maximum accumulation of Pb and Ni was observed in soils contaminated above the maximum permissible concentrations.